Student Team Learning in Practice (STEPs®): An Integrated Clinical Education Collaborative Model. Issue 2 (2017) - Covington, Kyle; Odom, Corrie; Heflin, Scott; Gwyer, Jan
Abstract : Background and Purpose. : Integrated clinical education (ICE) is the clinical component of the professional curriculum that is conducted concurrently with the didactic curriculum. Standardized, structured ICE experiences are now recommended to create a more robust curriculum for meaningful, early student learning. This purpose of this paper is to describe the development of an ICE curriculum that incorporates close clinical partnerships, explicit course curricula, and collaborative teams of students and clinical instructors (CIs). Method/Model Description and Evaluation. : The ICE curriculum model, Student Team Experience in Practice (STEPs®), consists of teams of students who learn with CIs trained to facilitate both group learning and individual student assessment. The ICE curriculum structure includes the following elements: direct patient care, planned learning experiences, guided reflections, skill assessment, and peer, self, and instructor assessment of behavioral objectives. The model is evaluated through student performance data, CI performance data, and satisfaction ratings from clinical faculty and students. The resources required for the model were also evaluated. Outcomes. : Greater than 95% of the 254 students received passing assessments for all skills and behavioral objectives in the STEPs® model, and the remaining students were successful after a remediation. The majority of students agreed or strongly agreed that they enjoyed learning in a collaborative team, that their team functioned well, that they exchanged constructive feedback, and experienced high levels of learning (93.7%‐98.2%). Students' ratings of their CIs were also positive, with greater than 97% of students indicating their CIs displayed favorable teaching characteristics always or frequently. Implementing STEPs® allowed a 70% decrease in the number of clinical sites needed, compared to the program's previous ICE program. Discussion and Conclusion. : The STEPs® model for early ICE has provided an opportunity for our program to more efficiently utilize clinical resources for delivering an ICE curriculum while enhancing student and instructor satisfaction. Additionally, the model has provided opportunities for students to demonstrate their individual performance in clinical practice across the didactic years of the curriculum.